Avaliação das mudanças de cobertura vegetal de áreas ribeirinhas na bacia do rio Vacacaí Mirim - Viega, Juliana Fernandes Vaz (2017)
The constant analysis of the condition of ciliary vegetation is fundamental in the management and conservation of natural resources as well as in the maintenance of local biodiversity. The main objective of this study is to detect and analyze the changes of vegetation cover of riparian areas in the Rio Vacacaí Mirim basin, in the state of Rio Grande do Sul, using the technique of Radiometric Rotation Controlled by Axis of Non-Change (RCEN). The RCEN technique allows the control of the digital algorithm of the detection of these changes, through the radiometric rotation of the multitemporal image and band of the visible spectrum, generating an image detection of these changes. In this study, images from the remote sensor Thematic Mapper - Landsat 5 were used to visualize and obtain information from research areas and GIS to perform RCEN procedures and image visualization. At work, pairs of images were analyzed, between the years of 2001 and 2011, in periods of 5 to 10 years, allowing the analysis of these changes over time. The resulting detection images, after statistical analysis, were categorized into three classes: degradation, preservation and recovery of vegetation cover. These results are based on the values of the pixels analyzed in each of the studied scenes: in the areas of degradation the pixels present themselves with positive (clearer) values, in the preservation areas the pixels present themselves with values close to zero and in the recovery areas present negative (darker) values. The analysis of the resulting cartographic material allowed a broader and more detailed view of the change of the scene along the Vacacaí Mirim basin, resulting from the impact of the anthropic actions suffered and the new landscape of soybean cultivation, replacing the bovine farming areas. In the study it was verified how much the basin was degraded during 10 years, but in the analysis of the drainage along the same approximately 30% of the same one was in stage of conservation and regeneration. Increasingly, the need for studies, monitoring and inspection of riparian areas, so important in maintaining the aquatic ecosystem, availability and quality of water and preservation of biodiversity, as a consequence, with the mandatory registration of all rural owners in the Environmental Registry Rural, demonstrating the importance of research.